Getting Ready for First Grade - Smith, Jodene (Summer Blast Ser., 2016)
Blast away learning loss for rising first grade students with fun theme-based units including language arts, mathematics, and critical and creative thinking activities. Support parents with everyday learning ideas and a handbook about today's standards.